What growing vegetables can do: experiences from Hoima, Uganda - Kiiza, Annet; Baguma, David; Mwanguhya, Joshua; Kasozi, Moses; Kabakoyo, Elizabeth; Turyahumura, Alex; Dickson Baguma, Sylvester; Kakeeto, Ronald; Ahumuza, Jasper; N’Danikou, Sognigbe; Recha, Tobias; Vernooy, Ronnie (2021)
This brief presents the main results and lessons learned from a pilot project to grow vegetables, diversify farming and improve livelihoods in the Hoima area of Uganda, coordinated by East West Seed Knowledge Transfer (EWS-KT), Bulindi Zonal Agricultural Research and Development Institute (BUZARDI) of the National Agricultural Research Organisation (NARO) of Uganda, the World Vegetable Centre, and the Alliance of Bioversity International and CIAT. Pilot farmers acquired new crop knowledge and management skills and successfully tested ten varieties of five vegetable species. They shared experiences and insights with more than a thousand fellow farmers from the district. Four vegetable production groups were formed that will continue and expand vegetable production.